Beyond Indigenous Religions in Indonesia: Struggling for their rights - Arifin, Ferdi (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
ndigenous religions in Indonesia include several registered organizations that struggle for their community rights. However, their struggle seems endless because the majority has insufficient knowledge and perspective of indigenous religions’ belief system. This study examines the process of their struggle historically to unveil their efforts to obtain their rights as citizens. Employing a qualitative method is suitable for this study because it utilizes literature reviews to understand the historical story of indigenous religions’ journey during their struggle. This study shows that the communities of indigenous religions should be paid attention by the government because the supreme council court of Indonesia has claimed legally their existence but the sub-institutions in each region cannot fully imply the legal standing of the decision.